Character-Based Thematic Learning: Integrating the Values of Honesty and Responsibility in Elementary Schools - Septiwiharti, Dwi; Hemafitria, Hemafitria; Wahab, Wahab; Putra, Purniadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research explores the integration of honesty and responsibility into thematic learning at MIS Nurul Yaqin Sambas and SD Inpres 6 Lolu, Palu City. Thematic learning, which combines various subjects through real-life contexts, provides a unique opportunity to instill character values in students. A qualitative case study approach was used, with data collected via observation, interviews, and document analysis. Observations focused on students' behaviors, while semi-structured interviews explored teachers' and students' experiences. Thematic analysis was applied, followed by data triangulation to ensure validity. The findings show that incorporating honesty and responsibility into thematic learning significantly improved students' awareness and behavior related to these values. Students demonstrated increased honesty and responsibility in their daily activities, while teachers played a crucial role by creating a supportive environment, using real-life examples, and recognizing positive behavior. This study suggests that integrating character values into thematic learning is an effective approach for elementary education, fostering students with strong moral and responsible character traits.